Potential of Pineapple (Ananas comocus (L.) Merr.) Flesh as a Laxative in Mice (Mus muscullus) - Sainal Edi Kamal; Muhammad Saharuddin; Jumrah Jumrah (Jurnal Farmasi Sandi Karsa, 2023)
The pineapple plant, Ananas comocus (L) Merr, has growing shoots at the base that grow into a midrib. The sword-like leaves are strong and substantial. For defecation, the bromelin enzyme, which is contained in pineapples, is frequently used as a laxative (constipation). The purpose of this study was to ascertain the laxative effects of pineapple flesh (Ananas comocus (L) Merr.) extract and the dosages at which it was effective. The Pharmacology Laboratory, Faculty of Mathematics and Natural Sciences, Pancasakti University, used an experimental study design. In this investigation, 25 mice were employed, split into 5 groups, starved for 1 hour, and then given loperamide to induce behavior. Na. CMC was used as a negative control in the first group, pineapple flesh extract was utilized in the second, third, and fourth groups at doses of 100 mg, 300 mg, and 500 mg, and dulcolactol was used as a positive control in the third and fifth groups. The Kruskal-Wallis test was used to examine the study's data and findings. According to the study's findings, pineapple flesh extract has a laxative effect. A dose of 500 mg is the laxative that works the best, with an average 2,1